Early development of primary care networks in the NHS in England: a qualitative mixed-methods evaluation. Issue 12 (30th December 2021) - Parkinson, Sarah; Smith, Judith; Sidhu, Manbinder
Abstract : Objectives: Primary care networks (PCNs) were introduced in the National Health Service (NHS) in England in 2019 to improve integrated care for patients and help address financial and workforce sustainability issues in general practice. The purpose of this study was to collect early evidence on their implementation and development, including motivations to participate and what enables or inhibits progress. This paper considers the core characteristics of PCNs, and how this informs their management. Design: A qualitative mixed-methods rapid evaluation was conducted across four case study sites in England, informed by a literature review and stakeholder workshop. Data collection comprised interviews, non-participant observation of meetings, an online survey and documentary review. Results: General practitioners (GPs) are motivated to participate in PCNs for their potential to improve patient care, enable better coordinated services and enhance financial and workforce sustainability within primary care. However, PCNs also have an almost mandatory feel, based on the national policy context and significant financial incentives associated with joining them. PCNs offer potential to bring GPs together to work towards common goals, deliver national priorities and respond rapidly to local needs. Conclusions: PCNs face similar challenges to other meso-level primary care organisations internationally, as they respond to local and national priorities and operate in a context of multiple goals and interests. In managing these organisations, it is important to find a balance between local and national autonomy, decision making and control.